2010
DOI: 10.4183/aeb.2010.361
|View full text |Cite
|
Sign up to set email alerts
|

A case of severe growth retardation, probably Seckel syndrome

Abstract: We report the case of a 6.6 years old boy, born to healthy unrelated parents, from a normal pregnancy, admitted for severe growth retardation. His height was 71 cm (-9.3 SD), with a weight of 6.6 kg and he presented a triunghiular face, mycrognatia, proeminent nose and hypertelorism resulting in a "bird headed" profile. He associated clinodactyly of the 5 th finger and a slightly longer left leg. Tanner stages were P1 G1. The biochemical panel was normal, but he presented mild hypocromic anemia. The thyroid fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Endocrine abnormalities are not well known in Seckel's Syndrome, but Dimitrescu et al reported an empty sella without pituitary deficits (26), and Di Blasi et al described a pituitary hypoplasia with lack in growth hormone (GH) stimulation (27). Deficit in corticotropin hormone or ACTH was observed by Kajantie et al (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endocrine abnormalities are not well known in Seckel's Syndrome, but Dimitrescu et al reported an empty sella without pituitary deficits (26), and Di Blasi et al described a pituitary hypoplasia with lack in growth hormone (GH) stimulation (27). Deficit in corticotropin hormone or ACTH was observed by Kajantie et al (28).…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the endocrine assessment was normal even for growth hormone under stimulation by glucagon propanolol test, and IGF1. The natural history of growth retardation and facial characteristics of Seckel's Syndrome raise some potential differential diagnoses, especially osteodysplastic primordial dwarfisms (OPDs) type I, II, and III and Russel-Silver's Syndrome (26). As our patient did not have any bone abnormality (except for kyphoscoliosis) the OPDs were not discussed.…”
Section: Discussionmentioning
confidence: 99%
“…It appears likely, that reduced IGF1 levels might rather be a reflection of severe IUGR without catch-up growth and low BMI [27] . Noteworthy, the endocrine state in patients with PCNT mutations has not been evaluated systematically, but IGF1 levels in Seckel and MOPD II patients have been reported occasionally to be normal [28] , [29] , elevated [30] , [31] or low [28] , [30] , [32] .…”
Section: Discussionmentioning
confidence: 99%